The Power of Culture in Building Trust and Loyalty: A Lesson Learned from COVID-19 Pandemic in Bali's Hotel Industry - Irene Hanna H. Sihombing; Diena Mutiara Lemy; Rudy Pramono (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
The COVID-19 pandemic severely impacted Bali's tourism sector, with international tourism declining by 99% in 2021 due to travel restrictions. Despite the dire circumstances, the hotel industry in Bali is recovering quickly. This study examines the effects of COVID-19 on organizational trust and employee loyalty in the tourism industry, focusing on long-term effects and post-pandemic recovery. A survey of 200 employees from three to five-star hotels in Bali assessed the impact on loyalty and the mediating role of organizational trust. Findings indicate that management's pandemic-related actions reduced employee loyalty due to decreased job security and heightened stress. Organizational trust declined during tourism uncertainty, particularly from early 2020 to mid-2022, but showed signs of recovery in 2023 and 2024. Results from expert interviews indicate that trust mitigated the pandemic's impact on employee loyalty, with the cultural values of the Hindu philosophy Tri Hita Karana playing a significant role in Balinese society. This study underscores the importance of organizational trust in maintaining employee loyalty post-crisis.